Pengolahan Limbah Medis COVID-19 Pada Rumah Sakit - Niki Tri Nurwahyuni; Laila Fitria; Olce Umboh; Dismo Katiandagho (Jurnal Kesehatan Lingkungan, 2020)
COVID-19 medical waste is residual material from unused reuse which is contaminated by substances that protect infectious or in contact with patients and/or hospital staff who need COVID-19 patients from service activities in the emergency room, isolation room, ICU room, treatment rooms, and other service rooms. The purpose of this study was to discover waste treatment in referral hospitals in North Sulawesi Province arising from the implementation of COVID-19 in 2020. The research was conducted on 18 of COVID-19 Referral Hospitals in North Sulawesi Province in period May - June 2020, by using cross-sectional as a research design. The results showed that 11 hospitals (61.1%) treated COVID-19 medical waste using their own incinerator, while 7 other hospitals (38.9%) treated COVID-19 medical waste using third-party services. All of the hospitals that treat medical waste using an incinerator do not fully have an operational permit from the Ministry of Environment and Forestry. The results obtained, in an emergency (COVID-19 pandemic), are excluded from having permission to use incinerators. All health facilities are expected to carry out the process of arranging incinerator operational permit documents coordinating with the Provincial / Regency / City Health Office and Provincial / Regency / City Environment Offices, even in the COVID-19 pandemic.